THE LEXICAL-SEMANTIC FIELD ‘FAMILY’ IN THE RUSSIAN LANGUAGE - Jurayeva Janona Saidjon qizi, (TADQIQOTLAR, 2026)
Abstract This article examines the lexical-semantic field “family” in the Russian language as an important fragment of the linguistic picture of the world. The study analyzes the structure of this  field, its  core  and periphery, as  well  as the semantic  relationships between the lexical units included in it. Particular attention is paid to the systemic relations  within  the  field,  including  hyperonymy,  synonymy,  and  derivational connections. The results of the research show that the lexical-semantic field “family” has  a  complex  multi-level  structure  and  reflects  the  cultural  and  social  values  of Russian society.